Hemophagocytic lymphohistiocytosis of a melanoma patient under BRAF/MEK-inhibitor therapy following anti-PD1 inhibitor treatment: a case report and review to the literature. Issue 1 (February 2021) - Dudda, Milena; Mann, Caroline; Heinz, Jaqueline; Schmidgen, Isabel; Weid, Florian; Kühn, M.; Saloga, Joachim; Grabbe, Stephan; Loquai, Carmen
Abstract : Hemophagocytic lymphohistiocytosis (HLH) is a rare but life-threatening condition. HLH in infants and young children is usually inherited, which is then classified as primary HLH. Secondary HLH, in contrast, is caused by many different conditions such as infections, cancer or medication and affects mostly adults. HLH is a hyperinflammatory condition, which may mimic an acute septic shock. We report on a 68-year-old patient with malignant melanoma with lymph node metastases. Due to the lymphogenic progression, treatment was switched from nivolumab to dabrafenib and trametinib. Twenty-one days after initiation of BRAF/MEK inhibitor therapy, the patient presented to our emergency department with clinical signs of infection such as fever and fatigue. Laboratory tests showed excessive inflammation levels without identifying an underlying pathogen. Two days later, the patient developed an increasing pancytopenia. After extending the diagnosis, we found very high ferritin levels, hypertriglyceridemia, hypofibrinogenemia and a soluble CD25 receptor. Based on the laboratory results, prolonged fever and splenomegaly, we were able to diagnose HLH as the underlying condition. We immediately initiated treatment with intravenous prednisone, which remarkably improved the clinical symptoms. After full recovery, we reinitiated anti-tumor treatment with vemurafenib and cobimetinib, which was tolerated without side effects. Due to the relatively nonspecific nature of the clinical signs and symptoms and the significant overlap with other diseases such as sepsis, the diagnosis of HLH is often delayed. This explains, in part, the high morbidity and mortality rate. Our case shows that early treatment with steroids is effective. However, much work remains in order to raise awareness and improve the understanding of the pathophysiology of this condition.